A Strategic Analysis of Monetary Interdependence - Hamada, Koichi (Journal of Political Economy, 1976)
Applying the monetary approach to the balance of payments, this paper examines the interdependent nature of monetary policies. In an n-country game where each monetary authority decides on its credit expansion to maximize its objective function, it is shown that the Cournot (or noncooperative) solution and the Stackelberg leadership solution do not lie on the contract curve, unless the aggregated preference over the balance of payments is exactly matched by the creation of international reserves. If the creation of international reserves exceeds the aggregated preference, the monetary expansion takes on the nature of public bads, leading to international inflation.